2017
DOI: 10.1063/1.4985878
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the water to boron nitride interaction: From zero to two dimensions with benchmark accuracy

Abstract: Molecular adsorption on surfaces plays an important part in catalysis, corrosion, desalination, and various other processes that are relevant to industry and in nature.As a complement to experiments, accurate adsorption energies can be obtained using various sophisticated electronic structure methods that can now be applied to periodic systems. The adsorption energy of water on boron nitride substrates, going from zero to 2-dimensional periodicity, is particularly interesting as it calls for an accurate treatm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 117 publications
13
67
0
Order By: Relevance
“…Interestingly, the binding energy of ASA on different 2D sheets considered in this study range from −0.52 to −0.70 for C1 configuration which is significantly larger than the binding energy of water on h‐BN and GRAP sheet. It is worth to mention that molecular adsorption on surfaces plays an essential role in corrosion, catalysis, water purification, gas storage and many other processes that are relevant to industry . From our results, it is clear that ASA strongly binds to the 2D sheets as compared to water, and hence, these 2D sheets can be used to remove aspirin molecules from waste water.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Interestingly, the binding energy of ASA on different 2D sheets considered in this study range from −0.52 to −0.70 for C1 configuration which is significantly larger than the binding energy of water on h‐BN and GRAP sheet. It is worth to mention that molecular adsorption on surfaces plays an essential role in corrosion, catalysis, water purification, gas storage and many other processes that are relevant to industry . From our results, it is clear that ASA strongly binds to the 2D sheets as compared to water, and hence, these 2D sheets can be used to remove aspirin molecules from waste water.…”
Section: Resultsmentioning
confidence: 69%
“…The study also reported that no practical charge transfer takes place between CNT (CNNT) and ASA. Moreover, Al‐Hamdani et al . studied the interaction of water with h‐BN of different dimensions (zero to 2‐dimensional) with benchmark accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The same system has recently been studied using diffusion Monte Carlo (DMC), the random-phase approximation (RPA), and dispersion functionals [40,41], as well as molecular MP2 [42] and periodic coupled cluster theory [43], demonstrating the need for reliable methods that can account for long-range van der Waals interactions and also to provide benchmark data. Furthermore, the recent work of Al-Hamdani et al [40] illustrates the importance of long-range correlation effects that account for approximately 25% of the reference adsorption energy computed in a (4 × 4) unit cell of h-BN. Figure 4 shows calculated adsorption energies at the level of RPA plus second-order screened exchange, MP2, CCSD, and CCSD(T) theories retrieved as a function of the number of atoms in the h-BN sheet.…”
Section: Resultsmentioning
confidence: 99%
“…Using MP2 theory, it is possible to study very large systems [40], and we find that the MP2 adsorption energy converges slowly to a thermodynamic limit value of 119 meV. We note that finite-size errors for adsorption energies on two-dimensional insulators are expected to decay as 1=N 2 , which is the predicted scaling from pairwise additive van der Waals interactions [40]. Applying the proposed finite-size correction to MP2 theory for the (4 × 4) unit cell h-BN sheet with 32 atoms yields an TABLE I.…”
Section: Resultsmentioning
confidence: 99%
“…10,16−19 In particular, the inclusion of beyond-pairwise dispersion interactions through the many-body dispersion (MBD) method coupled to semilocal DFT functionals has proven to be successful in this context. 10,15,20 To address larger length and time scales and more efficient structure prediction, several approximate electronic structure methods have been highly successful including semiempirical quantum chemical methods such as AM1, PM7, or the DFT-based densityfunctional tight binding (DFTB). 21−23 DFTB has been significantly improved recently, particularly in its description of charge polarization via third-order charge fluctuation corrections (DFTB3) 24,25 or its description of hydrogen bonding.…”
Section: −11mentioning
confidence: 99%